PENGARUH KEPEMIMPINAN TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KELURAHAN BAHU - Mundung, Joseph; Lengkong, florence Daicy; Tulusan, Femmy (Sam Ratulangi University, 2015)
Abstract : Economic progress, organizations and government agencies are increasingly rapidly thesedays makes human resources becomes a very important element for the progress of the organizationin terms of human resources such as, obedience work, the effectiveness and performance anddiscipline will be of benefit to an organization in the government when the led by a leader in order toachieve organizational goals. basically work discipline in the effectiveness of the organization has agoal to steer the behavior of subordinates with a number of regulations that support the achievementof objectives.Formulation of the problem in this research are: leadership influence what is being implementedby the employer in accordance with the perception of employees on the municipality's shoulder, howthe effectiveness of employees working on the municipality's shoulder, how much influence theleadership of the effectiveness of employees on keluraha shoulder. netode research used in thisresearch use descriptive research method. descriptive method qualitative research aims to describeand understand carefully the phenomena that will be made in research for hypothesis testingpurposes or to answer research questions and as a tool to control the variables that affect theresearch. the results of this study include: communication, responsibility, coaching and motivationcan be concluded that concludes the influence of leadership to the staff of the shoulder, veryinfluential in the spirit and work effectiveness due to the influence of environmental leadership in theravine the shoulder can make the effectiveness of the work in the shoulder become more disciplined,responsible for employment and more courteous in serving the community.Key words: Leadership, effectiveness